PROSPECTIVE EFFECT OF RED ALGAE, ACTINOTRICHIA FRAGILIS, AGAINST SOME OSTEOARTHRITIS AETIOLOGY - Sayed, Amany A.; Sadek, Shimaa A.; Soliman, Amel M.; Marzouk, Mohamed (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Osteoarthritis (OA) is a progressive disease characterized by joints pain and articular cartilagedestruction. Most of the current treatment strategies for OA are effective for symptoms relief but are accompanied withadverse side effect. Thus, the present investigation aims to evaluate the potential influence of red algae, Actinotrichiafragilis, in the dry powder form (AFP) or gel form (AFG) on some relevant factors of OA progression as well as assessits safety through in vitro and in vivo experiments.Materials and Methods: In vitro, AFP was analyzed for its chemical constituents screening, amino acid, proteinaseinhibitory activity, HRBC membrane stabilization activity, free radical scavenging activity, total antioxidant potency,nitric oxide radical scavenging power. In vivo, Organization for Economic Co-operation and Development (OECD)toxicity test was performed to test the safety of AFP on rats.Results: The present findings revealed that AFP and AFG can be considered as inflammatory-proteinase-oxidantinhibitor and considered to be safe according to the OECD guideline.Conclusion: AFP and AFG may have the potency to become the therapeutic candidate for OA disease as it preventsthe key causes of OA initiation.